Protease activated receptor signaling is required for African trypanosome traversal of human brain microvascular endothelial cells. - Dennis J Grab (Public Library of Science (PLoS), 2009)
Background Using human brain microvascular endothelial cells (HBMECs) as an in vitro model for how African trypanosomes cross the human blood-brain barrier (BBB) we recently reported that the parasites cross the BBB by generating calcium activation signals in HBMECs through the activity of parasite cysteine proteases, particularly cathepsin L (brucipain). In the current study, we examined the possible role of a class of protease stimulated HBMEC G protein coupled receptors (GPCRs) known as protease activated receptors (PARs) that might be implicated in calcium signaling by African trypanosomes. Methodology/principal findings Using RNA interference (RNAi) we found that in vitro PAR-2 gene (F2RL1) expression in HBMEC monolayers could be reduced by over 95%. We also found that the ability of Trypanosoma brucei rhodesiense to cross F2RL1-silenced HBMEC monolayers was reduced (39%-49%) and that HBMECs silenced for F2RL1 maintained control levels of barrier function in the presence of the parasite. Consistent with the role of PAR-2, we found that HBMEC barrier function was also maintained after blockade of Galpha(q) with Pasteurella multocida toxin (PMT). PAR-2 signaling has been shown in other systems to have neuroinflammatory and neuroprotective roles and our data implicate a role for proteases (i.e. brucipain) and PAR-2 in African trypanosome/HBMEC interactions. Using gene-profiling methods to interrogate candidate HBMEC pathways specifically triggered by brucipain, several pathways that potentially link some pathophysiologic processes associated with CNS HAT were identified. Conclusions/significance Together, the data support a role, in part, for GPCRs as molecular targets for parasite proteases that lead to the activation of Galpha(q)-mediated calcium signaling. The consequence of these events is predicted to be increased permeability of the BBB to parasite transmigration and the initiation of neuroinflammation, events precursory to CNS disease.